Riesgos De Salud Laboral Ante La Escasa Planificación De Estrategias Específicas De Preevención Y Aplicación Estricta De Las Normas Y Protocolos De Bioseguridad En El Hospital De Infectología “DR. José Daniel Rodríguez Maridueña” De La Ciudad De Guayaquil. - PIEDRA CHÁVEZ, . IVÁN HUMBERTO (2014)
To learn about the hospital and its effect on biosecurity areas of Surgery, ICU (Intensive Care Unit) and Emergency Hospital of Infectious Diseases "Dr. José Daniel Rodríguez Maridueña "city of Guayaquil during the period 2013-2014, a study was descriptive. The data collected in this study were obtained through the research tools, such as the descriptive survey guided health members who work within these areas, which together form the study group. The purpose of this research work is to recognize the practice of policy and methods of hygiene and biosecurity within hospitals so that by exposing this duct is to provide the staff of the Medical renewed about the primary rules biosafety according to each working section. Because of this, the present paper is oriented to hospital employees and thus create suitable to carry out its work within a range of security and appropriate prophylaxis.